2011
DOI: 10.1088/1009-0630/13/5/15
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond Repetitively Pulsed Dielectric Barrier Discharge in Air at Atmospheric Pressure

Abstract: Dielectric barrier discharge (DBD) between two cylindrical glass containers with salt water generated by a nanosecond repetitively pulsed power generator is reported. The electrical parameters, luminous images and spectrum diagnosis are presented. It is shown that the DBD possesses a large discharge current and an intense optical emission from the nitrogen second positive system below 400 nm. The gas temperature remains very close to room temperature regardless of pulse polarity. Luminous photographs with a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Specifically, a higher voltage amplitude will result in a higher concentration of plasma active particles. This should be attributed to the rise in degree of ionization by increasing the voltage in a certain range [26]. As for the peak value of the density of every particle in figure 3: the peak values of atom H, O, and electron of Case 3 are about 10.8, 4.3, and 4.5 times that of Case 1, respectively.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Specifically, a higher voltage amplitude will result in a higher concentration of plasma active particles. This should be attributed to the rise in degree of ionization by increasing the voltage in a certain range [26]. As for the peak value of the density of every particle in figure 3: the peak values of atom H, O, and electron of Case 3 are about 10.8, 4.3, and 4.5 times that of Case 1, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…equivalence ratio, mixture ratio) [23,24], pressure and temperature [12,22,25] were studied in related PAC experiments. While in the aspect of discharge operating variables, mainly the power type [26,27], amplitude of actuating voltage [28,29], discharge gap size [24], and actuating frequency [20,30] were analyzed. As one of the series studies, the influence of equivalence ratio on plasma assisted detonation initiation (PADI) has been studied in our preceding work [31], which showed that lowering the equivalence ratio will have an adverse effect on the benefits of plasma.…”
Section: Introductionmentioning
confidence: 99%
“…When the distance from the air gap increased to 4 mm, the discharge turned into an obvious filament-like discharge. He also compared single nanosecond pulse data, repeated nanosecond pulse data, and traditional Paschen curve [18,[25][26][27][28]. Lieberman developed a global model (volume-averaged) for argon and chlorine to investigate high-density, low-pressure electropositive and electronegative discharges under continuous wave and pulsed power excitation [29].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Except for the relatively early studies on the basic theory of PAC by DBD, most of the researches focus on the influences of discharge environmental parameters, such as the types of discharge gas, [7,12] gas flow rate, [13] ratio of fuel to oxidizer (e.g., equivalence ratio, mixture ratio), [14,15] pressure and temperature, [9,12,16] on the discharge plasma and combustion control. However, in the aspect of discharge operating parameters, especially the actuating frequency of an alternating current-dielectric barrier discharge (AC-DBD), [17,18] the relevant researches are still quite insufficient compared with the discharge environmental parameters. As one of the advantages of PAC, an active adjustment can be made easily through changing the discharge actuating frequency to realize an optimal effect on combustion control according to the practical situation.…”
Section: Introductionmentioning
confidence: 99%